Structure and function in rhodopsin: Rhodopsin mutants with a neutral amino acid at E134 have a partially activated conformation in the dark state - Kim, Jong-Myoung (The National Academy of Sciences of the USA, 1997)
The Glu-134–Arg-135 residues in rhodopsin, located near the cytoplasmic end of the C helix, are involved in G protein binding, or activation, or both. Furthermore, the charge-neutralizing mutation Glu-134 to Gln-134 produces hyperactivity in the activated state and produces constitutive activity in opsin. The Glu/Asp-Arg charge pair is highly conserved in equivalent positions in other G protein-coupled receptors. To investigate the structural consequences of charge-neutralizing mutations at Glu-134 and Arg-135 in rhodopsin, single spin-labeled side chains were introduced at sites in the cytoplasmic domains of helices C (140), E (227), F (250), or G (316) to serve as “molecular sensors” of the local helix bundle conformation. In each of the spin-labeled rhodopsins, a Gln substitution was introduced at either Glu-134 or Arg-135, and the electron paramagnetic resonance spectrum of the spin label was used to monitor the structural response of the helix bundle. The results indicate that a Gln substitution at Glu-134 induces a photoactivated conformation around helices C and G even in the dark state, an observation of potential relevance to the hyperactivity and constitutive activity of the mutant. In contrast, little change is induced in helix F, which has been shown to undergo a dominant motion upon photoactivation. This result implies that the multiple helix motions accompanying photoactivation are not strongly coupled and can be induced to take place independently. Gln substitution at Arg-135 produces only minor structural changes in the dark- or light-activated conformation, suggesting that this residue is not a determinant of structure in the regions investigated, although it may be functionally important.